2014
DOI: 10.1186/1471-2474-15-220
|View full text |Cite
|
Sign up to set email alerts
|

Local anaesthetic infiltration for peri-operative pain control in total hip and knee replacement: systematic review and meta-analyses of short- and long-term effectiveness

Abstract: BackgroundSurgical pain is managed with multi-modal anaesthesia in total hip replacement (THR) and total knee replacement (TKR). It is unclear whether including local anaesthetic infiltration before wound closure provides additional pain control.MethodsWe performed a systematic review of randomised controlled trials of local anaesthetic infiltration in patients receiving THR or TKR. We searched MEDLINE, Embase and Cochrane CENTRAL to December 2012. Two reviewers screened abstracts, extracted data, and contacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 74 publications
2
85
1
6
Order By: Relevance
“…In contrast, there are mixed opinions and conflicting results regarding the use of local infiltration analgesia after THA [54,65]. Marques et al [41] concluded that inclusion of local anesthetic infiltration in a multimodal anesthesia regimen is effective in reducing short-term pain and hospital stay for patients undergoing THAs and TKAs. However, Yin et al [65] stated that although local infiltration analgesia is a potential approach for reducing pain scores and analgesic consumption during the early postoperative stages without increasing risk of adverse effects, there was no indication that it could help in the later stages of recovery.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, there are mixed opinions and conflicting results regarding the use of local infiltration analgesia after THA [54,65]. Marques et al [41] concluded that inclusion of local anesthetic infiltration in a multimodal anesthesia regimen is effective in reducing short-term pain and hospital stay for patients undergoing THAs and TKAs. However, Yin et al [65] stated that although local infiltration analgesia is a potential approach for reducing pain scores and analgesic consumption during the early postoperative stages without increasing risk of adverse effects, there was no indication that it could help in the later stages of recovery.…”
Section: Discussionmentioning
confidence: 98%
“…Ropivacaine has become the preferred anaesthetic used for local infiltration analgesia in our institution although some recent trials report the use of bupivacaine and levobupivacaine [8]. We did not use adjuvant drugs such as ketorolac, steroids or adrenaline in Figure 2 Mean plasma ropivacaine concentrations at specified time intervals: (a) total; (b) free.…”
Section: Discussionmentioning
confidence: 99%
“…Wound catheters can be used to deliver additional local anaesthetic postoperatively [3] and allow analgesia to be extended beyond 24 h [4][5][6][7][8]. Despite the increasing popularity of such techniques, concerns have been expressed regarding the safety of injecting large volumes of local anaesthetic into knee joints during orthopaedic procedures [9].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a meta-analyses [13] reported the same type of positive impact on pain management after TKA when PAI was used. Liposomal bupivacaine (Exparel) was recently approved on the US market and has been used in several studies on TKAs to determine whether it might decrease pain or accelerate recovery after TKA.…”
mentioning
confidence: 99%